The Effect Of Leadership And Organizational Culture On Employee Performance With Employee Motivation As Variable Intervening At Pt.Telekomunikasi Indonesia (Telkom) In Batam - Cantika Dewi Ayu Ananda; Antony Sentoso (eCo-Buss, 2022)
PT. Telekomunikasi Indonesia Tbk, known as PT. Telkom is a State-Owned Enterprise which is engaged in providing technology, information and communication (ICT) services and the largest and most comprehensive telecommunications network in Indonesia. The business performance carried out by PT Telkom always increases, which comes from the Digital Business Telkomsel and the Indihome Brand, which even though in the midst of a pandemic like this, their income is still increasing and always growing. This study uses a type of quantitative research, namely the distribution of detailed and continuous questionnaires on a particular object within a predetermined period of time which includes the environment, where this method can identify the reality of an event as a variable that is influenced by the dependent variable and conduct an investigation of the variable. Based on the results of the author's survey at PT. Telekomunikasi Indonesia in Batam shows that leadership has an important role in the organization so that individuals carry out activities as expected by the organization. Organizational culture at PT. Telkom is able to have a direct impact on employee performance. In addition, the organizational culture at PT. Telkom is also able to increase employee motivation. Organizational culture at PT. Telkom can increase employee productivity and performance